Folktale Narratives and Economic Behavior - Igor Asanov; Dominik P. Heinisch; Nhat Luong (Philipps-University Marburg, School of Business and Economics, 2020)
Narratives - stories - prevail in social life, however little is known about their relation to economic behavior and outcomes. We shed light on this issue by studying the association between folktales' motifs and economic behavior across the world. First, we explore possible relations between the prevalence of narratives and the observed behavior in economic experiments by connecting the Berezkin (2015) collection of narratives with individual choices in experiments performed across the world. Second, we construct a motif distance index that approximates the cultural distance between countries. Third, we provide evidence that motif distance is associated with economic performance.
Keywords: 330; Volksglaube; Narrative Methode; Kulturelle Identität; Nationaleinkommen; Experiment; Welt